Validating Operational Food Insecurity Indicators Against a Dynamic Benchmark : Evidence from Mali - Christiaensen, Luc J. (World Bank, Washington, DC, 2014)
The authors develop an explicitly forward-looking indicator of food insecurity that takes into account both current dietary inadequacy and vulnerability to dietary inadequacy in the future. Application of this measure to data from northern Mali shows that neglecting the future dimension of food insecurity causes serious underestimation of food insecurity in this area. The authors evaluate the performance, relative to their dynamic bemchmark, of three readily available alternative indicators: an agricultural production index, a dietary diversity index, and a coping strategy index. Despite the uneven performance of these indexes relative to the individual components of the dynamic food insecurity indicator developed in the paper, they all demonstrate strong associations with that indicator. This is a promising result, given the urgent demand for reliable indicators of food insecurity.